Rekasi Pasar Modal Indonesia terhadap Pengumuman MSCI terkait Transparansi dan Free Float: Studi Peristiwa pada Saham LQ45 - Hasyidan Rifky Razan; Regina Jansen Arsjah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the reaction of the Indonesian capital market to the MSCI announcement regarding market transparency and free float through an event study on LQ45 stocks. This research uses a quantitative approach with the event study method. The event date is set on January 28, 2026, as t0, which represents the first trading day when the Indonesian capital market responded to the MSCI announcement. The observation period uses an 11-trading-day event window, consisting of five days before the event, one day on the event date, and five days after the event. The research sample was selected using a purposive sampling technique, resulting in 39 LQ45 companies that met the research criteria. The data used in this study are secondary data consisting of daily closing stock prices, the Jakarta Composite Index (JCI), stock trading volume, and the number of outstanding shares. Market reaction is measured using abnormal return, cumulative abnormal return, and trading volume activity. Expected return is calculated using the Market Adjusted Model, while hypothesis testing is conducted through normality tests and the Paired Sample t-Test. The results show that there is no difference in the average abnormal return of LQ45 stocks between the periods before and after the MSCI announcement regarding market transparency and free float. In addition, there is no significant difference in cumulative abnormal return between the periods before and after the MSCI announcement. However, the results indicate that there is a difference in the average trading volume activity of LQ45 stocks between the periods before and after the MSCI announcement. These findings indicate that the MSCI announcement was not significantly reflected in stock price changes, but was responded to by investors through increased stock trading activity.